EXPLORING STUDENT PERCEPTIONS ON ARTIFICIAL INTELEGANCE INTEGRATION IN ISLAMIC EDUCATION: A QUALITATIVE STUDY BASED ON BLOOM’S TAXONOMY AND THE TECHNOLOGY ACCEPTANCE MODEL - Abil Fida Muhammad Qois Al Hadi; Muh. Nur Rochim Maksum; Mutohharun Jinan; Viky Nur Vambudi; Ammar Wangyee (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The rapid development of Artificial Intelligence (AI) technology presents significant opportunities to enhance the quality of Islamic Religious Education (PAI). However, the implementation of AI in value-based education faces various technical, pedagogical, and ethical challenges that impact its effectiveness and sustainability. This qualitative phenomenological study explores students’ perceptions of AI integration in PAI learning, focusing on their experiences, acceptance, and challenges encountered. Data were collected through in-depth interviews and analyzed using the Technology Acceptance Model (TAM) and Bloom’s Taxonomy frameworks to understand acceptance levels and AI’s contribution to learning outcomes. Findings reveal that AI has the potential to support more personalized, adaptive, and interactive learning, especially at the cognitive and analytical stages. Nevertheless, the role of teachers and religious scholars remains essential in guiding spiritual aspects and value evaluation, positioning AI as a complementary tool rather than a replacement. Key challenges include overreliance, information validity, and ethical concerns, requiring adequate supervision and technology literacy. The study recommends AI integration grounded in Islamic values, involving religious experts, and curriculum development emphasizing critical thinking and originality. Thus, AI can become a strategic partner in creating relevant, humanistic, and ethical PAI learning in the digital era.